As-CATH4 and 5, two vertebrate-derived natural host defense peptides, enhance the immuno-resistance efficiency against bacterial infections in Chinese mitten crab, Eriocheir sinensis. Issue 71 (December 2017) - Guo, Zhilai; Qiao, Xue; Cheng, Ruomei; Shi, Nannan; Wang, Aili; Feng, Tingting; Chen, Yan; Zhang, Fen; Yu, Haining; Wang, Yipeng
Abstract: Host defense peptides (HDPs), a class of conserved components of animal innate immune system, possess direct antimicrobial activities against invading pathogens and broadly participate in boosting and modulating host immune responses. Cathelicidins is an important family of HDPs that has been identified exclusively in vertebrates. Considering the relatively conserved innate immune system between invertebrates and vertebrates, it is speculated that HDPs from vertebrates may also possess modulating functions on invertebrate innate immune system. In the present study, two novel cathelicidins (As-CATH4 and 5), which had been identified from the Chinese alligator in our previous study, were employed to investigate their functions as novel peptide immunostimulants in Chinese mitten crab. As-CATH4 and 5 exhibited potent, broad-spectrum, and rapid antimicrobial activities against all the tested aquatic pathogenic bacteria. Unlike traditional antibiotics, they target on bacterial cell membrane, induce membrane permeabilization and cell disruption, and ultimately result in cell death. The antimicrobial effect is far more rapid than traditional antibiotics. Therefore they are unlikely to induce bacteria resistance. After the crabs were administered with As-CATH4 and 5, the activities of lysozyme, acid phosphatase and alkaline phosphatase were significantly enhanced, which indicated that the immune system of crabs could be activated by As-CATH4 and 5. In bacteria challenge test, As-CATH4 and 5 could significantly decrease the bacterial numbers in crabs, and increase the survival rates of crabs in both pre-stimulation and co-stimulation groups. All of the results above indicated the great potential of As-CATH4 and 5 as novel peptide immunostimulants in the crab aquaculture. Highlights: The immunostimulatory function of two vertebrate-derived HDPs (As-CATH4 and 5) on Chinese mitten crab was studied. As-CATH4 and 5 exhibited potent, broad-spectrum, and rapid antimicrobial activities against aquatic pathogenic bacteria. As-CATH4 and 5 could significantly enhance the activities of lysozyme, acid phosphatase and alkaline phosphatase of crabs. As-CATH4 and 5 could significantly decrease the bacterial numbers in crabs and increase the survival rates of crabs. The results above indicated the great potential of As-CATH4 and 5 as novel peptide immunostimulants in crab aquaculture.